2020
DOI: 10.3390/ijms21249513
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-Preconditioned Human Adipose-Derived Stem Cells Enhance the Recovery of Oligodendrocyte-Like Cells after Oxidative Stress-Induced Damage

Abstract: Oxidative stress associated with neuroinflammation is a key process involved in the pathophysiology of neurodegenerative diseases, and therefore, has been proposed as a crucial target for new therapies. Recently, the therapeutic potential of human adipose-derived stem cells (hASCs) has been investigated as a novel strategy for neuroprotection. These cells can be preconditioned by exposing them to mild stress in order to improve their response to oxidative stress. In this study, we evaluate the therapeutic pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It is mainly due to an increase in their antioxidant capacity and bioenergetic regulation [ 31 , 32 ]. Furthermore, we showed that HC016-conditioned medium (CM) also increases their capacity to repair oxidative damage suffered by other cell lines, specifically in an in vitro model of oligodendrocyte-like cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly due to an increase in their antioxidant capacity and bioenergetic regulation [ 31 , 32 ]. Furthermore, we showed that HC016-conditioned medium (CM) also increases their capacity to repair oxidative damage suffered by other cell lines, specifically in an in vitro model of oligodendrocyte-like cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%